Applying in vivo expression technology (IVET)to the fungal pathogen Histoplasma capsulatum - Deepe Jr. G.S.; Woods, J.P.
Understanding how pathogens survive within the host cell is of paramount importance in the development of vaccines and therapeutic agents. This task has been particularly daunting in the study of fungal pathogens due to the lack of easily manipulated genetic systems. In recent years several molecular genetic reporter systems have been developed to identify genes expressed during the infection process and potential virulence determinants. The development of one method in particular, in vivo expression technology (IVET), has led to the discovery of several genes from various bacterial pathogens necessary for survival during infection. The recent development of molecular genetic tools for Histoplasma capsulatum has enabled us to adapt the IVET technology for this pathogenic fungus utilizing the URA5 gene, which is essential for H. capsulatum survival in mice and in cultured macrophages, as a reporter of in vivo gene expression. We report the first successful application of IVET screening of a fungal pathogen for genes expressed exclusively during infection.
Keywords: IVET; FUNGAL; DIFFERENTIAL GENE EXPRESSION; MOLECULAR GENETICS